(untitled) (Orfeu, 2021)
The aim of the current research was to investigate the nature of feedback when a digital technology system was introduced in the higher education (HE) piano studio alongside three teacher and student pairs in Brazil. Data were collected by using video-recorded observations of lessons, participant interviews, and also data related to the use of a specific technology. A thematic analysis of the resultant data suggests that participants used verbal and non-verbal feedback in three areas of lesson focus: music (score), performance (e.g., dynamics, articulation), and technology (Musical Instrument Digital Interface [MIDI] parameters). The application of technology seems to allow the focus of the lesson to become clearer, making students more aware of their performances and their learning processes. Data suggest that the engagement with technology varied across the three observed cases. There seems to be a valuable use for technology-mediated feedback; this could, in turn, optimize more traditional pedagogical approaches in HE piano learning and teaching, and also enrich private practice.